Verbal Interaction in Chemistry Secondary School Classrooms - Li, Winnie Sim Siew; Arshad, Mohammad Yusof (Sains Humanika, 2013)
Chemistry should be taught using inquiry approach to enhance understanding of concept of phenomena investigated. The way teacher implement inquiry teaching in chemistry classroom is vital as it affects the teaching and learning process. This study was carried out to investigate verbal interaction of chemistry teachers who applied inquiry approach in their chemistry lessons. Twenty three chemistry teachers and their pupils were involved in this study. Data collection method was mainly based on observation using Observation Instrument in Inquiry Teaching through Verbal Interaction (OIITVI), which was developed and modified based on previous existing classroom observation instruments. Even though the teachers claimed that they practiced inquiry, findings from this study showed that teachers are still dominating interaction in chemistry classroom. This research also revealed that percentage of teacher’s question is lower compared to teacher’s statement. Besides that, mean percentage of pupils’ questions has increased as observed in this research compared to previous researches. Nevertheless, teachers’ questions and pupils’ questions were found to be of low order thinking questions. Silence or confusion category contributes 37.0% of verbal interaction occurred in chemistry classrooms. Implication of this study showed that teachers should move towards creating inquiry-based classroom with focusing on quality pupil talk.